Making Use of Multiple (Non-shared) First Languages: State of and Need for Research and Development in the European Language Context - Meyer, Michael; Prediger, Susanne; César, Margarida; Norén, Eva (Mathematics Education and Language Diversity, 2015)
Wide empirical evidence and theoretical explanations show that first languages are important resources for increasing access to mathematics for learners whose first language is not the language of instruction. Whereas including the first language is well established in many countries outside Europe, especially those with shared first languages, most European classrooms deal with five or more (non-shared) first languages without making use of them. This chapter explores the specific European language context and its cultural, political, and institutional dimensions. We report practices of including first languages and report on European research into its effects and conditions.